Self-reported adherence to pharmacotherapy in cancer patients - Mir, Shakeel Ahmad; Bhat, Mehraj Ud-Din; Shakeel, Danish (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Medication adherence is a challenging issue. Non-adherence has been found to be associated with increased healthcare costs. Pharmacological anticancer therapies are increasingly shifting to oral medications. Oral therapy is more convenient and easier to administer but various issues are related to oral anticancer therapy, the prominent one being adherence. Methods: Single group, non-randomized, self-report study conducted from December, 2019 to February, 2020 in SKIMS Hospital, Kashmir. A novel medication adherence scale, General Medication Adherence Scale (GMAS) was used to assess the adherence. Results: The study population consists of 58.7% males and 41.3% females. 54.7% patients were illiterate and 45.3% patients were literate. 13.3% patients received one drug, 14.7% two drugs, 40.0% three drugs, and 32.0% received more than three drugs. 13.3% patients had poor, 9.3% low, 42.7% partial, 12.0% good and 22.7% high adherence. In low income group, 6.7% patients had poor, 6.7% low, 13.3% partial, 26.7% good and 46.7% high adherence. Among middle income group, 10.0% patients had poor, 10.0% low, 53.3% partial, 10.0% good and 16.7% high adherence. In high income group, 20.0% patients had poor, 10.0% low, 46.7% partial, 6.7% good and 16.7% high adherence. Conclusions: Most of the cancer patients were partially adherent to the prescribed medication. Various associated factors were gender, socio-economic status, literacy, and place of residence. Considerable variation in adherence was found in this study.